Significance of the Dead Sea Scrolls and other Essays Biblical and Early Christianity Studies from Malawi - Nkhoma, Jonathan S. (Oxford : Mzuni Press, 2013)
Jonathan Nkhoma, in this scholarly collection of essays, enriches the reader with different interesting windows on how one can unearth the riches contained in some of the New Testament writings. The first two essays underscore the importance of placing the New Testament in a proper context and attempt to construct this context by discussing the historical background and the theological understanding of the Qumran Covenanters as derived from the Dead Sea Scrolls. Jonathan Nkhoma treats many aspects touching the proper interpretation of the New Testament writings. For example, he shows how the s.
Chapter Eleven -- Ignatius: Martyrdom or Suicide? A Study inLight of His Letter to the Romans.
Description based on print version record.
Keywords: Dead Sea scrolls -- Congresses; Gentiles -- Congresses; Hellenism -- Congresses; Dead Sea scrolls; Dead Sea scrolls -- Relation to the New Testament; RELIGION / Judaism / General; Electronic books